Role benefits of the private practice midwife participation in national health insurance program - Ria Chitra Dewi; Ali Ghufron Mukti; Abdul Wahab (Jurnal Kesehatan Ibu dan Anak, 2020)
Since 2014, Indonesia has launched the National Health Insurance program (JKN) through the Social Security Agency (BPJS) to improve public health, including reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). It is expected all private health services including the private midwives are encouraged to participate in the JKN system. This study aims to determine the association between wage system with the participation of private midwives in JKN program. Case-control design was performed in this study. The subjects were private midwives in the Pekanbaru municipality, Indonesia. Private midwives who participated in JKN were determined as cases (45) while those who didn’t participate were identified as controls (45). Interview using structured questionnaire was conducted to collect quantitative data, while qualitative data was collected using indepth interviews. Chi-square and Odds Ratio with 95% Confident Interval were analysed to determine the association between midwives’ participation and benefits perception. The results showed that 85.6% of respondents indicated government reward incentives were lacking. The results of the analysis of statistical test Chi-Square obtained p-value of 0.001 with OR 16.0 (95% CI 1.98 to 129.27), which means midwives who participated in the program JKN were likely to have a sufficient reward perception 16 times greater than those who did not participate in the JKN.There is a relationship between private midwives’ participation in the JKN program with benefit system granted by the government.